2021
DOI: 10.1002/chem.202005221
|View full text |Cite
|
Sign up to set email alerts
|

Directing Polymorphism in the Helical Nanofilament Phase

Abstract: Herein, it is reported that the polymorphismin the helical nanofilament (HNF,B 4 )l iquid-crystallinep hase depends on the fabrication methods, that is, UV-driven formation andt emplate-assisted self-assembly in the nanoconfined geometry. As aresult, uniaxially oriented HNFs with different helical structures wereo btained, in which generation of the twisted-ribbon and cylindrical-ribbonp olymorphs showed that even the molecular lattice has ad ifferent orientation.T he detailed structures were directly observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…27−30 However, in previous studies, 18−23 the handedness of twisted domains and specific locations, in which chiral domains were formed, has not been wellcontrolled and scaled to large areas, and only the spontaneous emergence of domains was observed. In order to use the chiral structures of LCLC materials for sensor 31,32 or optical 33−35 applications fabricated by conventional chiral LC materials or solitonic structures in chiral nematic phases, 33−35 precise control of the handedness and microscopic placement of chiral domains is essential. In this study, we adopt micropatterned silicon wafers to induce periodically well-addressed air pillars, 36 which can induce a complete degenerate anchoring condition and periodic confinement effects on a millimeter scale.…”
Section: ■ Introductionmentioning
confidence: 99%
“…27−30 However, in previous studies, 18−23 the handedness of twisted domains and specific locations, in which chiral domains were formed, has not been wellcontrolled and scaled to large areas, and only the spontaneous emergence of domains was observed. In order to use the chiral structures of LCLC materials for sensor 31,32 or optical 33−35 applications fabricated by conventional chiral LC materials or solitonic structures in chiral nematic phases, 33−35 precise control of the handedness and microscopic placement of chiral domains is essential. In this study, we adopt micropatterned silicon wafers to induce periodically well-addressed air pillars, 36 which can induce a complete degenerate anchoring condition and periodic confinement effects on a millimeter scale.…”
Section: ■ Introductionmentioning
confidence: 99%
“…79 Practically all these filament-and nanocylinder-based B4 phase morphologies were realized by strategically incorporating chiral centers into the aliphatic side chains of bent-core molecules featuring up to three biphenyl segments (Figure 1). 74,76,77,79 Furthermore, all B4 nano-and microscale morphologies display a characteristic blue structural color (in reflection mode), 80,81 whose origin is not entirely understood but certainly linked to diffraction, scattering, or interference via the periodic nano-to microscale layering and packing of these filaments in thin films. 82 Single molecule stochastic dynamics (SD) atomistic simulations revealed that the position of the chiral center at the core-chain junction of these bent-core molecules either in the shorter meta-or the longer para-side of these asymmetric bent-shaped molecules imparted significant changes in the core-chain angle distributions as well as in the dihedral distribution functions of the first three bonds in the aliphatic side chain ψ 1 −ψ 3 (Figure 2).…”
mentioning
confidence: 99%
“…S1, ESI †). [33][34][35][36] When irradiated with unpolarized UV light, the azobenzene units undergo reversible photoisomerization. In the nematic and smectic C phase, polar directors of dimeric molecules are oriented along the direction of light irradiation to minimize light absorption (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S3, ESI †). 30,[33][34][35] Indeed, cooling the azobenzene dimers from the isotropic phase without UV irradiation results in the randomly oriented HNFs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation